Design of a Web-Based Academic Service System Using the Waterfall Method in the Information Technology Education Study Program - Michael Immanuel Simanullang; Mendarissan Aritonang; Edward Rajagukguk (PT FORMOSA CENDEKIA GLOBAL, 2025)
These issues affect the effectiveness of students in carrying out academic activities. As a solution, a web-based academic service application was developed with several main features, including the digital submission and management of academic letters to accelerate administrative processes, study program consultation services that enable real-time two-way communication between students and lecturers, and a digital academic archive that provides easy access to important documents such as internship reports, theses, and journals from previous students. The system was developed using the Waterfall method, which was implemented systematically through the stages of requirements analysis, design, implementation, and testing. The results of black-box testing showed that all features functioned properly according to user roles (admin, students, and lecturers).